2006
DOI: 10.2307/41166358
|View full text |Cite
|
Sign up to set email alerts
|

Managing Creativity in Small Worlds

Abstract: Although much has been written about psychological and social-psychological influences on creativity, 2 only recently have sociological approaches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(100 citation statements)
references
References 31 publications
4
94
0
2
Order By: Relevance
“…But location norm 1 can, at best, coexist with the previous one, but does not spread across the population. But the system can get 'stuck' in this state because the excessive cognitive proximity between firms and the homophilic behavior they foster generates a level of distrust that hinders openness and creative knowledge exchanges (Fleming and Marx, 2006;Nooteboom, 2006). As far as we know, many clusters can be affected by this type of situation where uncertainty and strong cognitive proximity prevent collective innovation and undermine cluster growth (Longhi, 1999;Appold, 2005;.…”
Section: Decision Externalities Under Uncertainty and Reputational Efmentioning
confidence: 99%
See 1 more Smart Citation
“…But location norm 1 can, at best, coexist with the previous one, but does not spread across the population. But the system can get 'stuck' in this state because the excessive cognitive proximity between firms and the homophilic behavior they foster generates a level of distrust that hinders openness and creative knowledge exchanges (Fleming and Marx, 2006;Nooteboom, 2006). As far as we know, many clusters can be affected by this type of situation where uncertainty and strong cognitive proximity prevent collective innovation and undermine cluster growth (Longhi, 1999;Appold, 2005;.…”
Section: Decision Externalities Under Uncertainty and Reputational Efmentioning
confidence: 99%
“…The first is about the rather low agglomeration speed, while the second relates to a weak fashion leader effect. Note that these two elements are often correlated in the case of clusters where the process of open technological collaboration needs a long time to occur, especially if gatekeeper firms are absent (Fleming and Marx 2006) or mistrust highly present. Along the same lines, the weakness of technological interdependence can be the consequence of too on the size of the population and the interaction structure between firms.…”
Section: Decision Externalities Under Strategic Complementarities Andmentioning
confidence: 99%
“…Small world researchers assert that structural holes and network cohesion need to coexist to impact positively on innovation and creativity. Small world network structure has both a high level of local tie strength and a large number of weak bridging ties at the periphery (Fleming andMarx, 2006, Uzzi andSpiro, 2005). Capaldo (2007) found that a network structure characterized by a large periphery of heterogeneous ties and a core of strong ties around a focal firm brought about substantial competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…This raises a discussion on which is the ideal network configuration for encouraging the emergence of creative ideas. Many contrasting proposals have been made, but a convergence seems to come forward on the idea that the best solution is that of a network consisting of a series of cohesive communities, which then facilitate intense exchanges, that have connections, even very weak, between them, which would help the dissemination new ways of thinking, thus avoiding the risk of excessive closure of a connected , but isolated, community which would remain stuck on what flows inside (Baggio, 2014a;Fleming & Marx, 2006). In such a configuration, then, the availability of highly standardized infrastructures and technologies increases the possibility of recombining different elements and simplifies the exchange of information and knowledge (Baggio, 2014b).…”
Section: Creative Processes As a Social Processesmentioning
confidence: 99%